Beyond carbon mechanisms: The role of energy service companies in strengthening energy transition policies and mitigating emissions - Vivi Arumita Sari; Jenniffer Jerica Lioe; Virginahlya Hilmarani Ratnaning Sarbana (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2025)
Background: The presence of carbon market mechanisms in Indonesia as a government solution to achieve emission reductions has proven to be ineffective. This ineffectiveness confirms that more effective and comprehensive alternatives are needed. In this case, ESCo can be one of the mechanisms that can encourage low-carbon development in Indonesia. Methods: This research framework uses a multi-method qualitative approach by combining a narrative literature review and document analysis related to the ESCo model and its effectiveness in reducing emissions. Findings: To address the low price of carbon in carbon trading and the prevalence of alleged phantom credits in REDD+ projects, ESCo emerges as a more measurable and stable mechanism. In fact, Indonesia has also launched regulations governing the implementation of ESCo through Ministerial Regulation No. 14 of 2016. However, the lack of social readiness, policy coherence, and suboptimal funding schemes have hampered the implementation of ESCo in Indonesia. Therefore, this paper provides several solutions by examining benchmarks from other relevant countries that can be adopted by the Indonesian government. Conclusions: The success of the ESCo scheme is determined not only by its business model but also by the synergy between public communication, policy reform, financing schemes, and public-private collaboration. Thus, ESCo in Indonesia can be a strategic step to ensure more tangible emission reductions in line with the Nationally Determined Contribution targets. By adopting best practices from other countries and mapping domestic implementation barriers, this study offers a comprehensive framework of solutions to optimize ESCo implementation for promoting low-carbon development in Indonesia. Novelty/Originality of this article: This article offers originality by presenting a comprehensive framework that integrates international best practices and domestic barrier analysis to optimize the implementation of the ESCo model as a more effective alternative to carbon markets for promoting low-carbon development in Indonesia.